Aspects Of Naming Of The Traditional Turkic Religion - Зууридинов, Өскөнбай; Кадыров, Медербек (Scientific Journal of Faculty of Theology, 2019)
From historical records we know that the turkic people had their own beliefs. But not a single historical writing recorded the name of the turkic beliefs. So the researchers tried to give a common name to the Turkic old beliefs. In this article we took a look at names of Turkic old beliefs given by researchers.